2004
DOI: 10.1128/jvi.78.12.6698-6704.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nodamura Virus Nonstructural Protein B2 Can Enhance Viral RNA Accumulation in both Mammalian and Insect Cells

Abstract: During infection of both vertebrate and invertebrate cell lines, the alphanodavirus Nodamura virus (NoV) expresses two nonstructural proteins of different lengths from the B2 open reading frame. The functions of these proteins have yet to be determined, but B2 of the related Flock House virus suppresses RNA interference both in Drosophila cells and in transgenic plants. To examine whether the NoV B2 proteins had similar functions, we compared the replication of wild-type NoV RNA with that of mutants unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 40 publications
5
65
1
Order By: Relevance
“…Additionally, titers of LV vectors encoding short hairpin RNAs could be rescued by cotransfecting NovB2 to the packaging cells. 21,40,49 As NovB2's mode of action is the unspecific binding of long dsRNA and subsequent protection against cytoplasmic Dicer-mediated cleavage, 21 it is likely that the gain in titer is the result of increased amounts of packageable genomic RNA (Supplementary Figure S3). Of note, the titer increasing effect was not only observed for GV and LV vectors but also for a multitude of transgenes supporting the hypothesis of rather unspecific protection of dsRNA Improving bidirectional vector performance T Maetzig et al Improving bidirectional vector performance T Maetzig et al against degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, titers of LV vectors encoding short hairpin RNAs could be rescued by cotransfecting NovB2 to the packaging cells. 21,40,49 As NovB2's mode of action is the unspecific binding of long dsRNA and subsequent protection against cytoplasmic Dicer-mediated cleavage, 21 it is likely that the gain in titer is the result of increased amounts of packageable genomic RNA (Supplementary Figure S3). Of note, the titer increasing effect was not only observed for GV and LV vectors but also for a multitude of transgenes supporting the hypothesis of rather unspecific protection of dsRNA Improving bidirectional vector performance T Maetzig et al Improving bidirectional vector performance T Maetzig et al against degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that size-independent dsRNA-binding proteins could act as silencing suppressors in insect and mammalian cells (5,9,14,28,33,55). The flock house virus B2 suppressor is a dsRNA-binding protein which interacts with the backbone of dsRNA as a dimer (10,35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, no morphological changes were observed in BHK21 cells transfected with purified NoV genomic RNA1 and RNA2 even at 24 hpt, when abundant RNA replication and progeny virus particles were detected (11). Furthermore, during the time course of this and our previous studies (14,47), cells expressing the NoV RdRp did not exhibit any of the morphological hallmarks of apoptosis, including cytoplasmic vacuolization, membrane blebbing, rounding, nuclear fragmentation, or detachment from the growth surface. Instead, in this study the cells appeared healthy for up to 24 hpt, and in a previous study they remained healthy for 12 days postinfection (47).…”
Section: Discussionmentioning
confidence: 95%
“…To determine whether the NoV RdRp localizes to mitochondria in cells, we used a well-defined reverse genetics system in which NoV RNA replication can be initiated in mammalian cells from cloned cDNA copies of the NoV genomic RNAs (14,47,69,72). For example, the entire replicative cycle can be initiated on expression of the NoV RNA1 and RNA2 cDNAs from T7 promoters in plasmid-transfected baby hamster kidney BSR-T7/5 cells (46) that constitutively express cytoplasmic T7 RNA polymerase (14,47). The replicative cycle launched from this system mirrors the kinetics seen during NoV infection (47).…”
Section: Expression and Localization Kinetics Of The Nov Rdrp In Tranmentioning
confidence: 99%
See 1 more Smart Citation